Recurrent autonomic dysreflexia; A case report and review of the literature - HARMAN, FERHAT (My University, 2023)
Autonomic dysreflexia is induced by spinal reflex mechanisms which continue to be intact in spite of the patient’s injury. Any proprioceptive or noxious stimuli below the injury level generates an afferent impulse. This initiates a generalized sympathetic response. In response, it results in vasoconstriction below the neurologic lesion. We present a case of a male patient with C6 ASIA-A tetraplegia who developed recurrent dysreflexic episodes which were relieved by replacing the clean intermittent catheterization by indwelling Foley catheterization.
Keywords: Autonomic dysreflexia; tetraplegia; rehabilitation